Recension av Pauli Rahkonen, Biblical Onomasticon Speaks - Eskhult, Mats (Svensk exegetisk årsbok, 2025)
Rahkonen has already proven his expertise in the field of name research through aDissertation on the Finnish substrate in geographical names in the southeastern contact area (2013).With this thesis, he wants to shed light on the connection between names in the biblical scripturesand archaeological findings. The book consists of one general section, "kappan", as well as fourpublished articles.